Developing Character Based Interactive Learning Media to Facilitate Students Self-Learning of Mathematics Capita Selecta (A research on mathematical critical and creative thinking skills of Mathematics department students of teachers training and educa - Ratnaningsih, Nani; Patmawati, Hetty (Proceeding of International Conference on Teacher Training and Education, 2016)
This research aims to design and develop a character based learning Interactive Media to Facilitate Students Â  Â self-learning of Mathematics Lecture Capita Selecta in developing Mathematical Critical and CreativeThinking skills of students. This research employs developmental research for one year from two years asplanned. Research methods and its study in the first year is started by theoretical studies conducted mainlyin literature and rational considerations, and empirical studies when the trials of character-based interactivemedia is designed to explore critical and creative thinking skills of students. Result of this study can bedrawn that the designed teaching materials are already able to direct students to discover concepts relatedto materials of Algebra, Quadratic Equations and Functions, and Systems of Linear Equations, and thegiven problems can explore critical and creative thinking skills of students. Teaching materials designed tobe interactive media is ready to use to facilitate self-learning of the students. The further research isimplementing capita selecta Mathematics as lecture using character-based interactive learning media tostudents who attend the lecture in order to determine the influence of media in developing interactivelearning critical and creative thinking skills of the students.